2018
DOI: 10.3389/fmed.2018.00214
|View full text |Cite
|
Sign up to set email alerts
|

Examining Cross-Age Experiences in a Distance-Based Intergenerational Music Project: Comfort and Expectations in Collaborating With Opposite Generation Through “Virtual” Exchanges

Abstract: There has been an increase in the number of music-based intergenerational programs conducted by music therapists as part of wellness and intergenerational music therapy programs. Research has shown that intergenerational music therapy programs have improved cross-age attitudes, interactions, and older adults' psychosocial well-being. Anecdotal evidence indicates that one of the challenges for creating music-based intergenerational programs is finding agencies that serve younger and older generations within clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 19 publications
(19 reference statements)
1
32
0
2
Order By: Relevance
“…Intergenerational asynchronous collaboration using an online platform was the focus of a study reported by Belgrave and Keown (2018). In their research, an established music therapy choir comprising older adults aged 61–79 collaborated in a project with a youth choir, aged 9–14.…”
Section: Resultsmentioning
confidence: 99%
“…Intergenerational asynchronous collaboration using an online platform was the focus of a study reported by Belgrave and Keown (2018). In their research, an established music therapy choir comprising older adults aged 61–79 collaborated in a project with a youth choir, aged 9–14.…”
Section: Resultsmentioning
confidence: 99%
“…Generally positive perceptions of the younger generation at the outset were also personally validated and substantiated after participating in the programme in two other studies (Barnard, 2014;Belgrave and Keown, 2018). Notably, one of the qualitative studies revealed a substantial positive shift in the older adults' perceptions of young people, from generally negative views at the beginning of the programme to a positive image of the youths as helpful and relatable (Santini et al, 2018).…”
Section: Cross-age Attitudes Comfort and Perceptionsmentioning
confidence: 79%
“…Six out of eight quantitative studies that statistically analysed the impacts of IE on cross-age attitudes, revealed their positive impact on older adults' perceptions of young people's skills and their personal qualities (e.g., teaching skills, trustworthiness; Gamliel and Gabay, 2014;Meshel and McGynn, 2004;Pinquart et al, 2000). Generally positive perceptions of the younger generation reported at the outset of the IE seemed to be validated and substantiated through participating in the programme (Barnard, 2014;Belgrave and Keown, 2018;Chapman and Neal, 1990;. Initially negative views were also improved substantially over the course of IE (Santini et al, 2018).…”
Section: Social Functioningmentioning
confidence: 93%
See 1 more Smart Citation
“…We therefore find teachers who do not take advantage of all of the benefits of using technology in music education and do not pass these benefits on to students (Belgrave & Keown, 2018; Calderón-Garrido et al, 2019; Creech, 2019; Johnson, 2017; Webster, 2002). The exception to this is score editors, which have proven to be an ally, not just when editing and digitising scores, but also when composing, listening, developing music reading skills and so on (Brodsky et al, 2008; Wöllner et al, 2003).…”
Section: Discussionmentioning
confidence: 90%